Experience with febuxostat in a patient with severe disabling gout - M. S. Eliseev; R. U. Shayakhmetova (Современная ревматология, 2017)
Gout is a chronic disease that frequently leads to disability if urate-lowering therapy is inefficient. The paper presents the positive experience with febuxostat, a novel non-purine xanthine oxidase inhibitor, in a young patient with disabling chronic tophaceous gout. Twelve-month therapy with daily 80-mg dose of febuxostat resulted in almost complete resorption of subcutaneous tophi and in a long-term lack of arthritis attacks with the persistent serum uric acid levels below target ones. This is the first experience in successfully switching from one to another xanthine oxidase inhibitor, which was described after febuxostat registration in the Russian Federation.